2020
DOI: 10.3390/ijerph17176250
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Collaboration for a Healthy Living Environment—Which Strategies to Implement, Why, and in Which Context?

Abstract: Background: Working toward a healthy living environment requires organizations from different policy domains and nongovernment partners involved in public health and the living environment to collaborate across sectors. The aim of this study is to understand how this cross-sector collaboration for a healthy living environment can be achieved. Methods: The realist evaluation approach was used to investigate what strategies can be used in which contexts to achieve cross-sector collaboration. The “Collaborative A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…For example, leadership in the respective organizations can promote a shared culture of care, long-term trusting relationships and key players as ‘bridge builders’ to build knowledge, attitudes and skills for sharing a common vision and language with all partners ( Martsolf et al., 2018 ). Thus, a multi-faceted approach is required to streamline procedural differences and increase interaction, understanding and respect between sectors ( Mikkelsen et al, 2013 ; van Vooren et al, 2020 ). Resolutions to procedural differences include shared personnel or resources, written agreements and holding regularly scheduled meetings made possible by policies, programmes and fundings that enable cross-sector partnerships ( Ladekjær Larsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, leadership in the respective organizations can promote a shared culture of care, long-term trusting relationships and key players as ‘bridge builders’ to build knowledge, attitudes and skills for sharing a common vision and language with all partners ( Martsolf et al., 2018 ). Thus, a multi-faceted approach is required to streamline procedural differences and increase interaction, understanding and respect between sectors ( Mikkelsen et al, 2013 ; van Vooren et al, 2020 ). Resolutions to procedural differences include shared personnel or resources, written agreements and holding regularly scheduled meetings made possible by policies, programmes and fundings that enable cross-sector partnerships ( Ladekjær Larsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A key recommendation was that the role of the health sector should be flexible, only leading intersectoral work if it matches the framing of the identified issue or problem. Subsequent case studies and scoping reviews have identified common success factors, such as building trust among partners, creating connections between different sectors through networks, providing clarity and accountability for roles and responsibilities, information-sharing, engaging the public, and understanding the local political context [ 22 , 23 , 29 , 34 37 ]. The UN Department of Economic and Social Affairs (UNDESA) released the SDG Partnership Guidebook, which describes successful partnerships for achieving the SDGs [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The transcripts were imported in the qualitative data analysis software program Atlas-Ti for data analysis [ 51 , 52 , 53 ]. Based on the initial program theories, a code tree was drafted by JB on possible coping strategies.…”
Section: Methodsmentioning
confidence: 99%